Learning from the Education Systems in Singapore and South Korea: Relevance and Implications for Educational Innovation in Indonesia in the Digital Era - Nuraini, Rizki Amalia; Dedi Kuswandi; Fikri Aulia; Endika, Yurdan Vebry (Journal of Practice Learning and Educational Development, 2025)
This study aims to analyze and synthesize the educational policies and practices of Singapore and South Korea, highlighting their relevance and implications for educational innovation in Indonesia in the digital era. Using a systematic literature review approach, data were collected from scholarly articles published between 2014 and 2024, focusing on educational policy, integration of digital technology, and the development of 21st-century skills. The findings reveal that Singapore emphasizes lifelong learning through initiatives like SkillsFuture Movement, while South Korea focuses on integrating digital technology into curricula and assessment systems. However, both countries face challenges, such as academic pressure in South Korea and societal preference for academic pathways in Singapore. Indonesia, while implementing Kurikulum Merdeka, still struggles with disparities in infrastructure, teacher competency, and access to technology. This comparative study underscores the importance of contextual adaptation of best practices from both countries to address Indonesia's unique challenges. The study recommends strengthening digital infrastructure, enhancing teacher training, and fostering a culture of lifelong learning to build a resilient and inclusive educational ecosystem in Indonesia.